Development and Validation of A Reverse Phase HPLC Method for the Analysis of Fluoxetine in Pharmaceutical Dosage Form - BONDE, C.G.; SARAVANAN, V.S.; L. WARE, AGASTI (Asian Journal of Chemistry, 2010)
A rapid and sensitive high performance liquid chromatographic method was developed for the estimation of fluoxetine in pharmaceutical dosage form. Fluoxetine was chromatographed on a reverse phase C18 column in a mobile phase consisting of methanol:water (40:60). The mobile phase was pumped at a flow rate of 1 mL/ min. The calibration curve was linear in the range of 1-10 μg/mL. The intra and interday variation was found to be less than 2 % showing high precision of the assay method. The mean recovery of the drug from the solution containing 10 μg/mL was 97 % indicating high accuracy of the proposed method. Due to its simplicity, rapidness, high precision and accuracy, the proposed method may be used for determining fluoxetine in bulk samples and pharmaceutical dosage forms.